The Influence Of Village Funds And Allocation Of Village Funds And Financial Assistance On Poverty Alleviation In East Kalimantan Province - Juliansyah Roy; Honip Bahrudin; Zamruddin Hasid (International Journal of Management Research and Economics, 2024)
The aim of this research is to determine and prove the effect of providing village funds, allocation of village funds and provincial financial assistance on the level of welfare of village communities in districts throughout East Kalimantan as viewed from a development economics perspective. The analytical method used in this research is a panel data regression model. Data processing techniques were carried out using the Eviews 7.0 computer program. The research results show that Village Funds have a positive and significant effect on poverty alleviation. This means that the greater the distribution of village funds, the more poverty alleviation programs in the village will increase; Allocation of village funds has a significant positive effect on poverty alleviation. This means that the greater the distribution of village fund allocations, the more poverty alleviation programs in the village will increase; Provincial financial assistance has a significant positive effect on poverty alleviation. This means that the greater the distribution of provincial financial assistance, the more poverty alleviation programs will increase; Village funds, village fund allocation and provincial financial assistance simultaneously have a significant effect on poverty alleviation. This means that the distribution of village funds, allocation of village funds and provincial financial assistance have a significant impact on poverty alleviation in villages.